Answer:
2310
Step-by-step explanation:
EXPLANATION:
To get the solution of the simultaneous equation, using the elimination method:
We will have the following steps:
Step 1:
Write the two equations:
![\begin{gathered} y=-\frac{1}{2}x+3 \\ y=-\frac{7}{2}x-3 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20y%3D-%5Cfrac%7B1%7D%7B2%7Dx%2B3%20%5C%5C%20y%3D-%5Cfrac%7B7%7D%7B2%7Dx-3%20%5Cend%7Bgathered%7D)
Step2: Subtract the two equations:
![\begin{gathered} y-y=-\frac{1}{2}x-(-\frac{7}{2}x)+3-(-3) \\ 0=-\frac{1}{2}x+\frac{7}{2}x+6 \\ \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20y-y%3D-%5Cfrac%7B1%7D%7B2%7Dx-%28-%5Cfrac%7B7%7D%7B2%7Dx%29%2B3-%28-3%29%20%5C%5C%200%3D-%5Cfrac%7B1%7D%7B2%7Dx%2B%5Cfrac%7B7%7D%7B2%7Dx%2B6%20%5C%5C%20%20%5Cend%7Bgathered%7D)
Step 3: Simplify the expression
![\begin{gathered} 0=3x+6 \\ 3x=-6 \\ x=-\frac{6}{3} \\ x=-2 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%200%3D3x%2B6%20%5C%5C%203x%3D-6%20%5C%5C%20x%3D-%5Cfrac%7B6%7D%7B3%7D%20%5C%5C%20x%3D-2%20%5Cend%7Bgathered%7D)
Step 4: Substitute x=-2 into the formula:
![\begin{gathered} y=-\frac{1}{2}x+3 \\ y=-\frac{1}{2}\times-2+3 \\ y=1+3 \\ y=4 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20y%3D-%5Cfrac%7B1%7D%7B2%7Dx%2B3%20%5C%5C%20y%3D-%5Cfrac%7B1%7D%7B2%7D%5Ctimes-2%2B3%20%5C%5C%20y%3D1%2B3%20%5C%5C%20y%3D4%20%5Cend%7Bgathered%7D)
Therefore, the answer is
![(-2,4)](https://tex.z-dn.net/?f=%28-2%2C4%29)
Thus,
Option B is correct
Answer:
3
Step-by-step explanation:
g